Intelligent PITB Trust Blockchain Model of Sentiment Analysis for the Decision-Making of Taverns Dynamic Recommendation System in China - Zhou , Wei; Salleh , Nor Zafir Md; Wang , Bolin; Jia, Zhihan; Ding, Yanfang (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Dynamic recommendations refer to personalized and real-time suggestions provided to users based on their current context, behavior, and preferences. One prominent concern is the potential invasion of user privacy. The need to collect and analyse vast amounts of user data for effective personalization raises ethical questions regarding the storage, security, and responsible use of sensitive information. This paper proposed a framework of the Psychometric Index Trust Blockchain (PiTB) model for the secure dynamic recommendation system for the hotel industry. The PiTB performs the decision-making process through the review of customers for the model prediction. With customer reviews, the Psychometric Index is computed for the reviews of the customer in the hotel with the uses of sentimental analysis. The PiTB model uses the trust mechanism for tanalyzehe security improvement in blockchain data for the application of sentimental analysis with use of psychometric indices. These indices serve as the foundation for a computer dynamic recommendation system, enabling real-time suggestions for hotel choices tailored to individual consumer preferences. Finally, a trust-based blockchain model is implemented for secure data processing in the online consumer in the hotel orders. The trusted blockchain model focused on the hotels dynamic recommendation system in China. Simulation analysis demonstrated that the proposed PiTB model achieves higher data security with effective dynamic recommendations to the customers of the hotel.